Perbandingan Strategi Pembelajaran Digital Antara Sekolah di Indonesia dan Singapura - Maya Kamilah; Siti Nurhayati; Afiyatun Kholifah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
The advancement of digital technology has driven significant changes in the field of education, especially in the Southeast Asia region. This study aims to compare the digital learning strategies used in Indonesia and Singapore through a comparative research method based on document analysis. Information was obtained from various government policies, official documents, research articles, and relevant digital publications. The results show that Indonesia prioritizes equitable access to technology, enhancement of digital skills for educators, and provision of educational facilities through national policies. In this context, Singapore focuses on technological innovation, development of technology-oriented education systems, and application of collaborative learning methods supported by integrated digital devices. The comparison reveals that Indonesia still faces challenges related to infrastructure and digital capabilities, while Singapore has achieved a more consistent level of digital development. This research provides in-depth insights into the advantages and difficulties faced by each country, serving as a guideline for future education digitalization policies.